Novel composite material for hot forging die and preparation method thereof

By using a composite material of CoCrNiCuFe high-entropy alloy matrix and TiB2 powder, combined with mechanical alloying and SPS sintering technology, the problem of hot-forged mold failure due to impact load and thermal fatigue is solved, and higher hardness and wear resistance are achieved, extending the mold life and improving production efficiency.

CN119776694APending Publication Date: 2025-04-08YANSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037227.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Hot forging molds are prone to deformation and failure due to huge impact loads and thermal fatigue stress during work, and internal metal flow leads to friction and wear, affecting product quality and production efficiency.

Method used

A composite material of CoCrNiCuFe high-entropy alloy matrix and TiB2 powder was prepared by mechanical alloying and discharge plasma sintering (SPS) technology, and 8wt.%TiB2 was added to improve the strength and wear resistance of the material.

Benefits of technology

It significantly improves the hardness and compression strength of hot forged molds, extends the service life of the mold, improves production efficiency and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a novel composite material for a hot forging die and a preparation method of the novel composite material. The preparation method comprises the following steps: preparing a CoCrNiCuFe high-entropy alloy matrix from the following components in percentage by mass: 2.039 wt% of Co powder, 1.799 wt% of Cr powder, 2.031 wt% of Ni powder, 2.199 wt% of Cu powder and 1.932 wt% of Fe powder through a mechanical alloying method; respectively weighing the powder in proportion in a glove box in an argon atmosphere; the sintering pressure is set to be 40 MPa, and the sintering temperature is set to be 1000 DEG C. The preparation method comprises the following steps: heating to 571 DEG C from room temperature at a heating rate of 137 DEG C / min, heating to 600 DEG C at a heating rate of 7 DEG C / min, preserving heat for 10 min, heating to a target sintering temperature at a heating rate of 70 DEG C / min, preserving heat for 10 min, unloading pressure, slowly cooling to room temperature to obtain a high-entropy alloy sintered body, and grinding and polishing the surface to obtain the block high-entropy alloy material. The prepared composite material for the hot forging die has more excellent hardness and wear resistance, and aims at solving the problem that the service life of the die is short in the using process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials and relates to a novel composite material for hot forging dies and a preparation method thereof. Background Art

[0002] Hot forging dies are mainly used for metal forging above the recrystallization temperature and are widely used in the machinery manufacturing industry. However, when the hot forging die is working, the huge external impact load and the thermal fatigue stress formed by repeated heating cause the die to deform and fail easily. The internal flowing metal causes strong friction on the forging mold cavity, causing the die to wear and fail easily. These factors will affect the quality of the output product blank. At the same time, the die needs to be repaired offline in time, which slows down the production rhythm and increases the labor intensity, seriously affecting the production efficiency [Liu Huatang, Zhou Wei. Research on Improving the Service Life of Wheel Forging Dies [J]. Shanxi Metallurgy, 2021, 44(03): 66-69.]. This requires that the hot forging die material has high strength, hardness, wear resistance and oxidation resistance. Therefore, the development of a wear-resistant, high-temperature and high-strength hot forging die composite material to replace the original die steel can improve the service life of the die, effectively improve production efficiency and reduce production costs. The CoCrCuFeNi high entropy alloy structure is composed of ductile dual FCC phases, which has excellent toughness and plasticity but no excellent strength and hardness. CoCrCuFeNi-based multicomponent alloys with Y2O3 addition (Y2O3wt.%=0, 1, 2 and 3) were synthesized by mechanical alloying. After vacuum hot pressing (VHP) consolidation, the microhardness of the CoCrCuFeNi composite material increased significantly from 370±6HV to 548±5HV when the Y2O3 addition amount was increased from 0wt.% to 3wt.%. 14.2 Cr 2.7The formation of Y2 particles can prevent the migration of grain boundaries during sintering, resulting in an increase in the hardness of these alloys [Rao KR, Alshgari RA, Bahajjaj AAA, et al. Effects of Nano Scale Y2O3 Additions on Microstructural Stability and Mechanical Properties of Equiatomic CoCrCuFeNi Based High Entropy Alloys[J]. Materials Chemistry and Physics, 2023, 296: 127325.]. Titanium diboride (TiB2) has the characteristics of high melting point, high strength and hardness, high elastic modulus, good thermal conductivity, chemical stability and thermal shock resistance, and is one of the ideal HEAs reinforcements. Xiao Daihong et al. prepared 5 vol.% TiB2 reinforced AlCoCrFeNi based composites by spark plasma sintering (SPS) technology, and investigated the effects of sintering temperature and sintering pressure on the microstructure and properties of the composites. The study found that under the sintering conditions of 1200℃ and 30-45MPa, the composites were composed of BCC, B2, FCC, σ and TiB2 phases. When the sintering conditions were 1200℃ / 30MPa, the density of the composites reached 99.6%, the yield strength reached 1474MPa, the compressive strength reached 2416MPa, and the hardness exceeded 470HB [Xiao Daihong, Liu Yu, Yu Yongxin, et al. Effect of spark plasma sintering on the microstructure and properties of TiB2 / AlCoCrFeNi composites [J]. Materials Engineering, 2018, 46(03): 22-27.].

[0003] Because HEA has a cocktail effect, the CoCrNiCuFe matrix itself has high strength and hardness, high plasticity and toughness, excellent corrosion resistance and high temperature oxidation resistance, but when used in hot forging die materials, pure HEA cannot meet the application requirements of the die material. After adding TiB2, the strength, hardness, wear resistance and oxidation resistance of the composite material can be further improved, but too high TiB2 content will also cause the brittleness of the composite material to increase significantly and reduce plasticity, so the TiB2 content plays a vital role in enhancing the performance of CoCrNiCuFe-based composite materials. Summary of the invention

[0004] The object of the present invention is to provide a composite material for hot forging dies with higher hardness and wear resistance and a preparation method thereof.

[0005] The chemical mass percentage of the CoCrNiCuFe high entropy alloy matrix in the present invention is: Co powder 2.039 wt.%, Cr powder 1.799 wt.%, Ni powder 2.031 wt.%, Cu powder 2.199 wt.%, Fe powder 1.932 wt.%. The purity of all metal powders is 99%, and except for the particle size of Cu powder being 45 μm, the particles of other metal powders are all ≤5 μm. CoCrNiCuFe powder is prepared by mechanical alloying using a high-energy ball mill. The ball milling jar is a steel jar, and steel balls with diameters of 10 mm, 8 mm, and 6 mm are used, the mass ratio of large, medium, and small balls is 6:3:1, the ball-to-material ratio is 10:1, and the mass of the steel balls loaded in the jar is 100 g. In a glove box filled with argon, weigh the raw material powder and put it into a steel ball mill (volume 250 ml), add 0.4 ml of anhydrous ethanol as a dispersant, seal the ball mill, and then place it on a high-energy ball mill for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 30 h. Stop for 2 h for heat dissipation after every 5 h of rotation. Stop the machine every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the jar and mix them evenly. Then add 0.4 ml of anhydrous ethanol to the jar and continue ball milling. In a glove box with argon atmosphere, CoCrNiCuFe powder and TiB2 powder (8-10wt.%) were weighed according to the set ratio and loaded into a high-energy ball mill steel jar. Steel balls with diameters of 10mm, 8mm and 6mm were added according to a ball-to-material ratio of 10:1. The mass ratio of each steel ball was 6:3:1. 0.1ml of anhydrous ethanol was added as a dispersant. The ball mill jar was sealed and then placed on a high-energy ball mill for mixing. The ball mill speed was set to 200r / min and the mixing time was 2h. After mixing, the powder was sieved through 80 mesh in a glove box with argon atmosphere. The mixed composite powder was placed in a glove box and allowed to stand for 10h in preparation for sintering.

[0006] The mixed CoCrNiCuFe-TiB2 hot forging die composite powder is placed in a glove box, and 3-5g of the composite powder is weighed with an electronic balance and loaded into a graphite mold with an inner wall covered with 32.5mm×45mm×0.2mm graphite paper. The assembled mold is pre-pressed with a spinning machine and pre-pressed for 30s at 30MPa. The hot forging die composite material is prepared using a spark plasma (SPS) sintering test machine. The pre-pressed graphite mold is placed in the center of the upper and lower pressure heads of the SPS sintering furnace, and axial pressure is applied at 30-50MPa. Sintering begins when the furnace chamber vacuum is less than 100Pa. The sintering process uses infrared temperature measurement, and the temperature is raised from room temperature to 600℃ in 5min and kept warm for 5min. After the insulation is completed, argon is filled to -0.05Pa, and then the temperature is raised to the target temperature at 70℃ / min and kept warm for 10min. After sintering, when the temperature in the cabin drops below 60°C, the pressure is released, the cabin door is opened, the mold is taken out, the sintered block is removed from the mold, and the surface is ground and polished to obtain a hot forging mold composite material sintered body. DETAILED DESCRIPTION

[0007] Example 1

[0008] The CoCrNiCuFe high entropy alloy matrix was prepared by mechanical alloying. According to mass percentage, Co powder is 2.039 wt.%, Cr powder is 1.799 wt.%, Ni powder is 2.031 wt.%, Cu powder is 2.199 wt.%, and Fe powder is 1.932 wt.%. CoCrNiCuFe powder was prepared by mechanical alloying using a high energy ball mill. In a glove box with argon atmosphere, 9.2g CoCrNiCuFe powder and 0.8g TiB2 powder were weighed according to the set ratio and loaded into a high-energy ball mill steel jar. Steel balls with diameters of 10mm, 8mm and 6mm were added according to the ball-to-material ratio of 10:1. The mass ratio of each steel ball was 6:3:1. 0.1ml of anhydrous ethanol was added as a dispersant. The ball mill jar was sealed and then placed on a high-energy ball mill for mixing. The ball mill speed was set to 200r / min and the mixing time was 2h. After mixing, the mixture was sieved through 80 mesh in a glove box with argon atmosphere. The mixed composite powder was placed in a glove box and allowed to stand for 10h in preparation for sintering.

[0009] The mixed hot forging die was filled with composite materials into a graphite die pre-installed with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 30 MPa for 30 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was sintered for SPS sintering experiment. The sintering pressure was set to 40 MPa and the sintering temperature was 1000 °C. The temperature was increased from room temperature to 571 °C at a heating rate of 137 °C / min, from 571 °C to 600 °C at a heating rate of 7 °C / min, and kept at 600 °C for 10 min. The temperature was increased from 600 °C to the target sintering temperature at a heating rate of 70 °C / min and kept at 600 °C for 10 min. Then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a high entropy alloy sintered body. The surface of the prepared sintered body was ground and polished to obtain a bulk high entropy alloy material.

[0010] After the obtained high entropy alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:

[0011] The prepared composite materials for hot forging dies have good comprehensive performance, and their hardness and compressive strength have great advantages over traditional metals. Example 2

[0012] The CoCrNiCuFe high entropy alloy matrix was prepared by mechanical alloying. According to mass percentage, Co powder is 2.039 wt.%, Cr powder is 1.799 wt.%, Ni powder is 2.031 wt.%, Cu powder is 2.199 wt.%, and Fe powder is 1.932 wt.%. CoCrNiCuFe powder was prepared by mechanical alloying using a high energy ball mill. In a glove box with argon atmosphere, 9.0g CoCrNiCuFe powder and 1.0g TiB2 powder were weighed according to the set ratio and loaded into a high-energy ball mill steel jar. Steel balls with diameters of 10mm, 8mm and 6mm were added according to the ball-to-material ratio of 10:1. The mass ratio of each steel ball was 6:3:1. 0.1ml of anhydrous ethanol was added as a dispersant. The ball mill jar was sealed and then placed on a high-energy ball mill for mixing. The ball mill speed was set to 200r / min and the mixing time was 2h. After mixing, the mixture was sieved through 80 mesh in a glove box with argon atmosphere. The mixed composite powder was placed in a glove box and allowed to stand for 10h in preparation for sintering.

[0013] The mixed hot forging die was filled with composite materials into a graphite die pre-installed with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 30 MPa for 30 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was sintered for SPS sintering experiment. The sintering pressure was set to 40 MPa and the sintering temperature was 1000 °C. The temperature was increased from room temperature to 571 °C at a heating rate of 137 °C / min, from 571 °C to 600 °C at a heating rate of 7 °C / min, and kept at 600 °C for 10 min. The temperature was increased from 600 °C to the target sintering temperature at a heating rate of 70 °C / min and kept at 600 °C for 10 min. Then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a high entropy alloy sintered body. The surface of the prepared sintered body was ground and polished to obtain a bulk high entropy alloy material.

[0014] After the obtained high entropy alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:

[0015] The prepared composite materials for hot forging dies have good comprehensive performance, and their hardness and compressive strength have great advantages over traditional metals. Example 3

[0016] The CoCrNiCuFe high entropy alloy matrix was prepared by mechanical alloying. According to mass percentage, Co powder is 2.039 wt.%, Cr powder is 1.799 wt.%, Ni powder is 2.031 wt.%, Cu powder is 2.199 wt.%, and Fe powder is 1.932 wt.%. CoCrNiCuFe powder was prepared by mechanical alloying using a high energy ball mill. In a glove box with argon atmosphere, 8.8g CoCrNiCuFe powder and 1.2g TiB2 powder were weighed according to the set ratio and loaded into a high-energy ball mill steel jar. Steel balls with diameters of 10mm, 8mm and 6mm were added according to the ball-to-material ratio of 10:1. The mass ratio of each steel ball was 6:3:1. 0.1ml of anhydrous ethanol was added as a dispersant. The ball mill jar was sealed and then placed on a high-energy ball mill for mixing. The ball mill speed was set to 200r / min and the mixing time was 2h. After mixing, the mixture was sieved through 80 mesh in a glove box with argon atmosphere. The mixed composite powder was placed in a glove box and allowed to stand for 10h in preparation for sintering.

[0017] The mixed hot forging die was filled with composite materials into a graphite die pre-installed with graphite pad paper, and pre-pressed by a hydraulic press at a pressure of 30 MPa for 30 s. The pre-pressed powder was then dried at 50 °C for 2 h. The obtained prefabricated sample was sintered for SPS sintering experiment. The sintering pressure was set to 40 MPa and the sintering temperature was 1000 °C. The temperature was increased from room temperature to 571 °C at a heating rate of 137 °C / min, from 571 °C to 600 °C at a heating rate of 7 °C / min, and kept at 600 °C for 10 min. The temperature was increased from 600 °C to the target sintering temperature at a heating rate of 70 °C / min and kept at 600 °C for 10 min. Then the pressure was unloaded and the temperature was slowly cooled to room temperature to obtain a high entropy alloy sintered body. The surface of the prepared sintered body was ground and polished to obtain a bulk high entropy alloy material.

[0018] After the obtained high entropy alloy block material was polished, the organization and performance were tested using instruments used in conventional testing methods. The obtained technical parameters are as follows:

[0019] The prepared composite materials for hot forging dies have good comprehensive performance, and their hardness and compressive strength have great advantages over traditional metals.

[0020] The results of the above examples are analyzed, and it is found that the composite material with 8wt.% TiB2 added has the best performance. The present invention can prepare a new type of hot forging die composite material with excellent performance through the raw material and preparation method.

[0021] The present invention is described above by way of example, but the present invention is not limited to the details of the above embodiments, and the present invention can be implemented in other specific forms without departing from the basic features of the present invention. Any changes or modifications made based on the present invention belong to the scope of protection claimed by the present invention.

Claims

1. A new composite material for hot forging dies, characterized in that: The composite material powder for the hot forging die is prepared by mixing CoCrNiCuFe powder and TiB2 powder, and the chemical mass percentage of the CoCrNiCuFe high entropy alloy matrix is: Co powder 2.039 wt.%, Cr powder 1.799 wt.%, Ni powder 2.031 wt.%, Cu powder 2.199 wt.%, Fe powder 1.932 wt.%; in a glove box with argon atmosphere, 9.2g CoCrNiCuFe powder and 0.8g TiB2 powder; 9.0g CoCrNiCuFe powder and 1.0g TiB2 powder; 8.8g CoCrNiCuFe powder and 1.2g TiB2 powder are weighed respectively according to the set ratio.

2. The novel composite material for hot forging dies according to claim 1, characterized in that: The purity of all metal powders is 99%. Except for the Cu powder with a particle size of 45 μm, the particle size of other metal powders is ≤5 μm. The purity of the TiB2 powder is 99.5% and the particle size is 3 μm.

3. A method for preparing a new composite material for hot forging dies as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1. CoCrNiCuFe powder was prepared by mechanical alloying using a high-energy ball mill. The ball mill was a steel mill with steel balls of diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls was 6:3:1, the ball-to-material ratio was 10:1, and the mass of the steel balls in the mill was 100 g. In a glove box filled with argon, the raw material powder was weighed and put into a steel ball mill with a volume of 250 ml. 0.4 ml of anhydrous ethanol was added as a dispersant. The ball mill was sealed and then placed on a high-energy ball mill for ball milling. The ball mill speed was set to 350 r / min and the ball milling time was 30 h. The mill was stopped for 2 h for heat dissipation every 5 h. The raw material adhering to the grinding balls and the inner wall of the mill was scraped off and mixed every 10 h. Then 0.4 ml of anhydrous ethanol was added to the mill to continue ball milling. S2. In a glove box with an argon atmosphere, CoCrNiCuFe powder and 8-10wt.% TiB2 powder were weighed according to the set ratio and loaded into a high-energy ball mill steel tank. Steel balls with diameters of 10 mm, 8 mm and 6 mm were added according to a ball-to-material ratio of 10:

1. The mass ratio of each steel ball was 6:3:

1. 0.1 ml of anhydrous ethanol was added as a dispersant. The ball mill was sealed and then placed on a high-energy ball mill for mixing. The ball mill speed was set to 200 r / min and the mixing time was 2 h. After mixing, the mixture was sieved through 80 mesh in a glove box with an argon atmosphere. The mixed composite powder was placed in a glove box and allowed to stand for 10 h in preparation for sintering. S3. Put the composite powder prepared in S2 in a glove box, weigh 3-5g of the composite powder with an electronic balance and load it into a graphite mold whose inner wall is wrapped with 32.5mm×45mm×0.2mm graphite paper; pre-press the assembled mold with a spinning machine and pre-press it for 30s at 30MPa; use a spark plasma sintering test machine to prepare the hot forging mold composite material, put the pre-pressed graphite mold into the center of the upper and lower pressure heads of the SPS sintering furnace, apply axial pressure of 30-50MPa, and start sintering when the vacuum degree of the furnace chamber is lower than 100Pa; infrared temperature measurement is used during the sintering process, and the temperature is raised from room temperature to 600℃ in 5min and kept warm for 5min. After the insulation is completed, argon is filled to -0.05Pa, and then the temperature is raised to the target temperature at 70℃ / min and kept warm for 10min; after the sintering is completed, wait until the temperature in the cabin drops below 60℃, release the pressure, open the cabin door and take out the mold to obtain a sintered body of the hot forging die composite material.

4. The method for preparing a new composite material for hot forging dies according to claim 3, characterized in that: The blank of the hot forging die composite material sintered body is subjected to surface grinding and deburring treatment to obtain the composite material for the hot forging die.